“Concealed Weapons.” The Napa Valley Register, November 10, 1880, p. 3 - (:unkn) unknown (General Publisher, 1880)
Prohibited the concealed carry of any dirk, pistol, sword-cane, sling-shot, or other dangerous or deadly weapon. Violators guilty of a misdemeanor, and shall be fined not less than ten nor more than one hundred dollars. Violators imprisoned until fine is paid, not to exceed one day for each dollar fined.
--
Keywords: CARRY - CONCEALED